Physical and Mechanical Properties of Non-Woven Thermal-Bonded Materials (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The influence of the main technological parameters and the content of modifiers and plasticizers on the physical and mechanical properties of non-woven thermally bonded materials has been studied. The optimal values for the content of binder, plasticizer, modifier, catalyst and thermal bonding conditions have been established.